Dynamics of mast cells in lymph node following antigenic stimulation - Dabak, DO; Aydin, G; Ozguner, M (Wiley, 2004)
Dynamics of mast cells in rat cervical lymph nodes were examined using conventional histological techniques after injection of Salmonella paratyphi B-H antigen. There was no significant change in the number of mast cells at sixth hour and on the first day of stimulation compared with the controls. The number of mast cells was increased in all lymph node compartments on the second day of stimulation, which continued in the following 3 days. On the eighth day of stimulation, although the mast cell number decreased in the subcapsular area, it was still high in the paracortical area and medullary sinuses of the lymph nodes. On the second day of stimulation, the mast cell number was apparently increased in the subcapsular area than those of the other compartments. In the following days of stimulation, the highest number of mast cells was seen in the medullary sinuses. The highest paracortical mast cell number was determined on the third day of stimulation and some mast cells were observed near the high endothelial venules (HEVs). The changes of mast cell number among the lymph node compartments after antigenic stimulation support the hypothesis that the migration of mast cells occurred. This migration pattern indicates that mast cells enter the lymph node via afferent lymphatics and migrate to the lymph node compartments following antigenic stimulation.
Keywords: Peritonitis; Recruitment; Involvement; Expression; Migration